A functional neuro-anatomical model of human attachment (NAMA): Insights from first- and second-person social neuroscience. (May 2020) - Long, Madison; Verbeke, Willem; Ein-Dor, Tsachi; Vrtička, Pascal
Abstract: Attachment theory, developed by Mary Ainsworth and John Bowlby about seventy years ago, has become one of the most influential and comprehensive contemporary psychology theories. It predicts that early social interactions with significant others shape the emergence of distinct self- and other-representations, the latter affecting how we initiate and maintain social relationships across the lifespan. A person's attachment history will therefore associate with inter-individual differences in emotional and cognitive mechanisms sustaining representations, modeling, and understanding of others on the biological and brain level. This review aims at summarizing the currently available social neuroscience data in healthy participants on how inter-individual differences in attachment associate with brain anatomy and activity across the lifespan, and to integrate these data into an extended and refined functional neuro-anatomical model of human attachment ( NAMA ). We first propose a new prototypical initial attachment pathway and its derivatives as a function of attachment security, avoidance, and anxiety. Based on these pathways, we suggest a neural attachment system composed of two emotional mentalization modules (aversion and approach) and two cognitive mentalization modules (emotion regulation and mental state representation) and provide evidence on their functionality depending on inter-individual differences in attachment. We subsequently expand this first-person social neuroscience account by also considering a second-person social neuroscience perspective comprising the concepts of bio-behavioral synchrony and particularly inter-brain coherence. We hope that such extended and refined NAMA can inform attachment theory and ultimately help devising new prevention and intervention strategies for individuals and families at risk for attachment-related psychopathology.